Revisit to the Accuracy of Arcuate eminence as a Surgical landmark for Superior semicircular canal in Middle cranial fossa surgeries - Swathi, B. Sriparna; Prasad, K. C.; G, Induvarsha.; N. S, Ashwini.; Manjunath, Deepthi; S, Gautham. (Journal of Neonatal Surgery, 2025)
Introduction- The arcuate eminence is a well-recognized anatomical landmark on the petrous part of the temporal bone and has historically been used as a reference point for identifying the superior semicircular canal. Precise localization of the superior semicircular canal is critical in otologic and neurotologic surgeries. It is used in surgery of the middle cranial fossa as a reference point to locate the internal acoustic canal within the temporal bone. This study aims to evaluate the anatomical precision of the arcuate eminence as a surface landmark for the superior semicircular canal, with a distinct focus on determining the part of the canal that is exposed. Materials and methods – A cross sectional study was done on 20 dry temporal bones from February 2025 till April 2025. The bones were dissected in the Temporal bone dissection lab of department of Otorhinolaryngology & Head and Neck surgery, R L Jalappa Hospital, Tamaka, Kolar. The arcuate eminence in these specimens is recognized as a small, raised ridge or rounded elevation located near the midpoint of the petrous part of the temporal bone. Meticulously drilling Over the Arcuate Eminence to gradually thin the bone,the ivory coloured bony outline of the SSC start to appear. The canal will appear as a curved, hollow structure within the petrous bone. The angle formed between the long axis of the arcuate eminence and the tangential line connecting the petrous apex to the superior petrosal sinus will be analysed. Additionally, the distance from the arcuate eminence to the inner part of squamous part of temporal bone also analysed. These are measured with the help of a divider, protractor and ruler. Results- Doom of superior semi circular canal was corresponding to arcuate eminence in 11 specimens (55%) and not corresponding to arcuate eminence in 9 specimens (45%). The angle between the arcuate eminence and the superior petrosal sulcus varied among specimens, with a mean angle of 37.65°. The distance between the arcuate eminence and the inner squamous part of the temporal bone showed variability, with a mean distance of 19.9 mm Conclusion- The current study reaffirms that while the arcuate eminence is often used as a superficial landmark for locating the superior semicircular canal during middle cranial fossa surgeries, its accuracy as a reliable and consistent guide is limited..